Metode Role Playing Dalam Meningkatkan Motivasi Berprestasi Anak Usia Dini Selama Masa Learning From Home - Nuryati Nuryati; Muthmainnah Muthmainnah; Hilda Zahra Lubis; Sitti Rahmawati Talango; Busthomi Ibrohim; Difla Nadjih (UIN Sultan Maulana Hasanudin Banten, 2021)
Achievement motivation is the urge to do the best possible, in order to obtain the best results in accordance with the expected conditions, by trying hard, and outperforming others based on certain quality standards. The low development of achievement motivation of children aged 4-6 years and the application of the role playing method still uses limited media. The purpose of this study is to describe how to provide achievement motivation, and how children respond when giving achievement motivation. The methodology used in this study is a literature study that describes how the role-playing method is used in TK ABA Buntu Dea, Tongko Village. Data collection techniques used are observation, interviews, and documentation. The results of research through the role playing method can affect achievement motivation in early childhood because with achievement motivation children can get to know each other's characteristics better, and increase self-confidence. Thus the role playing method is considered effective as a learning method to increase achievement motivation in early childhood.